Menjadi “Filosof Muslim” di Media Sosial: Referensi dari Husein Ja’far Al-Hadar - Husin Lubis, Zakaria (UIN Sumatera Utara, 2023)
This article is of the view that the presence of philosophy in cyberspace, especially YouTube, has eliminated the